Teaching and learning strategies in remote education: A systematic review of the literature - Rozo, Hugo; Ramírez-Montoya, María Soledad (Australasian Journal of Educational Technology, 2025)
Remote education is an alternative delivery modality for digital environments, responding to several societal requirements and the needs of today’s education. Although the term has been used since the early 2000s, the COVID-19 pandemic forced it to emerge as a temporary alternative to continue the educational processes during confinement. However, the research and interest have persisted. This research analysed the remote experiences reported in the literature, emphasising the teaching and learning strategies and the technologies used to support them. A systematic literature review using the PRISMA protocol identified 51 articles from the Scopus and Web of Science indexing databases. The analysis and synthesis involved categorisation and classification guided by research questions directed towards the review objective. The findings revealed that (a) remote experiences use diverse strategies, predominantly active methodologies that privilege the experiential; (b) technologies support the remote strategy development, but the use or intention of the technology is not always straightforward; (c) some studies note strategies mediated by remote and cyber-physical labs, artificial intelligence and teaching assistants; (d) general interest in the topic exists in all areas, disciplines and educational levels, predominantly higher education; and (e) it is necessary to follow up on remote experiences after pandemics. This research adds value through its observations that, more than an emergency alternative, remote education is a pillar of hybrid education and future education. Implications for practice: Faculty designed remote experiences based on active methodologies and enabled by technologies, which impacted learning. This suggests that it is possible to carry out a quality educational process in remote. The COVID-19 pandemic accelerated the transformation of education in the multimodal forms of delivering learning experiences to meet the needs of contemporary society. Universities recognise the potential of remote learning to address issues of access and reach, while also enhancing hybrid and flexible learning models.